Development, validation and implementation of a quantitative food frequency questionnaire to assess habitual vitamin D intake. Issue 4 (17th January 2016) - Kiely, M.; Collins, A.; Lucey, A. J.; Andersen, R.; Cashman, K. D.; Hennessy, Á.
Abstract: Background: A well‐designed, validated quantitative food frequency questionnaire (FFQ) could offer an efficient and cost‐effective method for assessing habitual vitamin D intake. The present study aimed to describe the development, validation and implementation of a vitamin D FFQ. Methods: National food consumption survey data obtained from Irish adults (18–64 years) were used to identify foods that contribute 95% of vitamin D intake. A winter‐based validation study was carried out for the resulting FFQ in 120 females, including 98 women [mean (SD) 65.0 (7.3) years] and 22 girls [12.2 (0.8) years], using a 14‐day diet history (DH) as a comparator. Serum 25(OH)D concentrations were analysed. Validity coefficients were calculated using the method of triads. Cross‐classification and Bland–Altman analysis were also performed. Results: Median (interquartile range) vitamin D intakes (including the contribution from nutritional supplements) were 5.4 (3.7) and 3.7 (5.9) μg day −1 from the FFQ and DH, respectively and intakes of vitamin D from food sources were 3.6 (3.1) and 2.4 (2.2) μg day −1 . The FFQ and DH classified 86% and 87% of individuals into the same and adjacent thirds of wintertime serum 25(OH)D status, respectively. There was a strong association ( r = 0.71, P < 0.0001) and no significant systematic or proportional bias observed for the difference between estimates from the FFQ and DH. The validity coefficient for the FFQ was 0.92 (95% confidence interval = 0.80–0.97). Repeatability analysis ( n = 56) performed 6–12 months later showed no significant difference in estimates of vitamin D between administrations. Conclusions: The data obtained in the present study indicate high validity and good reproducibility of a short, interviewer‐administered FFQ for vitamin D.